Evaluación agronómica y productiva de cebolla colorada (Allium cepa L.) a diferente dosis de fertilización química y orgánica, en el sector el batan, cantón Riobamba, provincia de Chimborazo - Chuto Mala, Ana Rebeca (2022)
The present investigation proposes: To evaluate agronomically and productively the red onion (Allium cepa L.) at different doses of chemical and organic fertilization, in the Batan, Riobamba canton, Chimborazo province. The objectives of the investigation were: i) To evaluate agronomically and productively the red onion (Allium cepa L) at different doses of chemical and organic fertilization ii) Determine the characteristics agronomic and productive characteristics of the red onion in each of the fertilizers. iii) Evaluate in which of the doses of fertilizers the red onion presents better agronomic and productive characteristics. iv) Compare the results of the red onion to chemical and organic fertilization. v) Carry out an economic analysis of the relationship benefit cost B/C. A completely randomized block design (DBCA) was applied, with 8 treatments and 3 repetitions: Two types of fertilizers, chemical and organic (Ecoabonaza) each with a different dose: the recommended, + 15%, - 15% and two witnesses. These were applied in three seasons: at transplant, Dap and Ecoabonaza, at 40 DDT urea and Ecoabonaza, and 80 DDT potassium muriate and Ecoabonaza. Each experimental unit had 6 rows, each one with 20 seedlings, for the evaluation of the variables 10 plants were taken at random from each experimental unit. The best yield in the chemical fertilizer was, the Chemical + 15% and in the case of the fertilizer organic, was Ecoabonaza + 15%, with a yield of 43.9 and 35.38 Tn/ha respectively, the components that contributed to performance were: percentage of capture at 8 and 15 DAT, number of leaves and height of the plant at 30, 60 and 90 DDT, polar and equatorial diameter, bulb weight, number and thickness of cataphylls that were taken at harvest. The best cost-benefit ratio was for Chemical + 15% with $1.23. The harvest was carried out at 126 DAT. In the crop cycle there was an indecency of pests such as: Mildiu, Alternaria in the stage of crop development and Cutters in the first days after transplanting.